Nutritional status and health of community-dwelling older adults in urban areas of the Lalitpur district, Nepal - Eebaraj Simkhada; Aerusha Simkhada (PLoS ONE, 2026)
Background Poor nutrition causes ill health and functional dependence in the older population. Different aspects of older people’s health and nutritional status are little known in the growing older population in Nepal. This study describes the nutritional status, socio-demographic factors, and health-related characteristics among community-dwelling older people in urban areas of Lalitpur district of Nepal. Methods The study was a cross-sectional population-based study among older people aged 60 years and older, in five Village Development Committees (VDCs) around the outskirts of Lalitpur Metropolitan City of Lalitpur district of Nepal. Multi-stage cluster sampling with probability proportional to size was used to select a sample of 360 old aged individuals. Nutritional status was assessed by the Mini Nutritional Assessment (MNA) tool. The data on socio-demographic factors, socioeconomic factors, and health characteristics were presented in percentages, means, and standard deviations. Chi-square and ANOVA tests were performed to assess the associations of variables with malnutrition. Results Using the MNA score, this study found 13% malnutrition and 45% at risk of malnutrition among participants. About 28% of the study population was overweight with a body mass index (BMI) > 25.0. About one-fourth (25.6%) were totally dependent financially on their children. Approximately 62.2% were diagnosed with chronic diseases. Hypertension was the most prevalent disease (26.5%), followed by Diabetes Mellitus. About 28.6% reported insomnia, and 18.6% of individuals reported having chronic pain. Agriculture as an occupation, increased age, hospitalization within a year and having insomnia were significantly associated with nutritional status in bivariate analysis. Conclusions About half of the population had poor nutritional status. Old-aged individuals were suffering from chronic diseases, chronic pain, insomnia, and financial dependency. This study indicates an urgent need to take care of health of the older people with timely intervention at the community and national level.